Jordan Left Derivations of Generalized Matrix Algebras (Communications in Mathematical Research, 2021)
In this paper, it is proved that under certain conditions, each Jordan leftderivation on a generalized matrix algebra is zero and each generalized Jordan leftderivation is a generalized left derivation.